THE IMPACT OF COVID-19 OUTBREAKS ON INDONESIA’S AUTOMOTIVE AND PAPER INDUSTRY STOCK RETURN - Thalia, Madeline; Suhendah, Rousilita (Graduate Program of Universitas Tarumanagara, 2023)
This study was carried out to identify the effect of COVID-19, Large-Scale Social Restriction policies, market capitalization, and stock trading volume on the company's stock returns from 2 March 2020 to 30 December 2020. The subjects in this study are companies in the automotive and component industries as well as the pulp and paper industry which are listed on the Indonesia Stock Exchange (IDX) during 2020. This study uses 3 theories, namely the Signaling Theory, Efficient Market Hypothesis Theory, and Black Swan Theory. Panel data regression analysis was used in the study, using EViews 9 program and Microsoft Excel to process all data. Results show that growth of COVID-19 positive cases and market capitalization have a significant negative effect on the company's stock return. The other results show that the increasing of LSSR (Large-Scale Social Restriction) policies and stock trading volumes have an impact on increasing company’s stock returns, while the growth of death cases of COVID-19 has no impact on increasing or decreasing company’s stock returns.